Court mediation reform : efficiency, confidence and perceptions of justice - Ali, Shahla F. (Edward Elgar Publishing, 2018)
As judiciaries advance, exploring how court mediation programs can provide opportunities for party-directed reconciliation whilst ensuring access to formal legal channels requires careful investigation. Court Mediation Reform explores comparative empirical findings in order to examine the association between court mediation structure and perceptions of justice, efficiency and confidence in courts. This unique study draws on an eighty-three person survey as well as case studies from ten global mediation jurisdictions including Australia, France, Hong Kong, India, and the United States. Given the highly contextual nature of court mediation programs, the book highlights the achievements, challenges and lessons learned in the implementation of mediation programs for general civil claims. In so doing, the study identifies that positive achievements are largely dependent on multiple factors including the functioning of the civil litigation system, the capacities of the mediators, safeguards against bias, participant education, and cultural and institutional support. This book will be of interest to both scholars and practitioners of law, civil justice, mediation, comparative law and dispute resolution. It will also be of use to judiciaries and policy makers looking to advance court mediation programs.